2021
DOI: 10.1029/2020ja028916
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Unexpectedly Localized Slowing of the Thermospheric Cross‐Polar Jet of Neutral Wind Over Alaska in the Midnight Sector

Abstract: Earth's thermosphere is the region of atmosphere from E  90 km up to E  500-1,000 km altitude depending on solar-cycle conditions. Its lower edge is defined by the transition to a positive vertical temperature gradient above the mesopause, whereas the upper limit is generally taken to be the height at which the mean free path exceeds one scale height. The upper portion of the thermosphere corresponds to the altitude region occupied by low Earth-orbiting spacecraft. Understanding the details of the weather in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…On 1 February 2019, observations show the occurrence of the cross‐polar jet inside the polar cap (Itani & Conde, 2021). On the other hand, as shown in Figure 10b, simulations indicate that equatorward winds were stalled and a high‐temperature region occurred over southeastern Alaska, forcing the neutral winds to turn poleward through the pressure gradient force.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On 1 February 2019, observations show the occurrence of the cross‐polar jet inside the polar cap (Itani & Conde, 2021). On the other hand, as shown in Figure 10b, simulations indicate that equatorward winds were stalled and a high‐temperature region occurred over southeastern Alaska, forcing the neutral winds to turn poleward through the pressure gradient force.…”
Section: Discussionmentioning
confidence: 99%
“…We use the model results at pressure surface level Z p = 1, which is close to the ∼240 km altitude where the 630.0 nm emission from atomic oxygen is observed by the ground‐based Doppler spectroscopy. We conducted TIEGCM simulations of 12 individual cases, as observed in Itani and Conde (2021), to investigate the driving mechanisms of thermospheric wind stalling and the dates for 12 cases were given in Column 1 of Table 1. All simulations were preconditioned for 20 days to reach a steady state.…”
Section: Model Descriptionmentioning
confidence: 99%
“…This emission layer itself extends below 200 km and above 300 km in altitude and can vary based on background conditions (Ogawa et al., 2002), thus is most sensitive to long vertical wavelengths. The SDI data consist of 115 different look regions in the sky, retrieving U and V wind components (Conde & Smith, 1995, 1998; Itani & Conde, 2021). For this study of LSTAD perturbations, data from 19 January were used starting at ∼2 UT.…”
Section: Observationsmentioning
confidence: 99%
“…These secondary GWs exhibit horizontal scales that are much larger than those of the primary GWs (Vadas et al, 2018). Itani & Conde (2021) investigated an abrupt stalling of the cross-polar jet in the midnight sector over Alaska. They reported that the characteristic length scale of the stalling could be as short as ∼200 km.…”
Section: Introductionmentioning
confidence: 99%